Numeracy Literacy of Spatial Geometry: A Case Study of Elementary School Teacher - Nurafni (EduMatSains : Jurnal Pendidikan, Matematika dan Sains, 2026)
This study aims to describe the numeracy literacy of mathematics teachers in teaching spatial geometry at Ruhama Islamic Elementary School. Numeracy literacy is a fundamental competence that influences teachers’ ability to interpret and apply mathematical concepts in classroom instruction. This study employed a qualitative descriptive approach involving two fifth-grade teachers as research subjects. Data were collected through numeracy literacy tests and semi-structured interviews. The validity of the data was ensured through triangulation techniques. Data analysis followed the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings reveal that the first subject was able to use various numbers but experienced difficulties in understanding mathematical symbols. The subject was also misled by visual representations, resulting in incorrect interpretation and decision-making. In addition, the subject demonstrated weaknesses in unit conversion and basic multiplication. Meanwhile, the second subject was able to use numbers and mathematical symbols related to basic operations and showed an ability to analyze given information. However, the subject lacked depth in interpreting information, leading to errors in answering several questions. In conclusion, both subjects exhibited limitations in numeracy literacy, particularly in interpreting visual information and applying mathematical concepts accurately. Therefore, future research should investigate the underlying factors contributing to these difficulties and explore strategies to enhance numeracy literacy among elementary school teachers